Barbarian sentiments : how the American century ends - Pfaff, William, 1928- (New York (19 Union Square West, New York 10003) : Hill and Wang, 1989)
Examines the cost of forty years of American world engagement and of American ideological clashes with the politics of various nations.
Includes index.
Keywords: United States -- Foreign relations -- 1945-1989.; United States -- Foreign relations -- 1945-1989.